Chinese firm dynamics and the role of ownership type: A conditional estimation approach of the Asymmetric Exponential Power (AEP) density - Matthias Duschl; Shi-Shu Peng (Philipps-University Marburg, Department of Geography, 2014)
This paper investigates the impact of ownership type on the entire growth rate distributional mass of Chinese firms, using a conditional estimation approach of the Asymmetric Exponential Power (AEP) density that goes beyond simple location-shift analysis. We first find a Chinese growth puzzle, i.e., a deviation from the stylized fact of the variance-scaling relationship commonly found in Western European economies. We then find, through five hypotheses, that the ownership type mainly affects the tails of the growth rate distributions. Our results also indicate that barriers of becoming a high growth firm, such as financial constraints, are especially prevalent in the Chinese private sector.
Keywords: C46; O53; L10; 330; firm growth; growth rate distributions; AEP conditional estimation; variance-scaling relationship; China; ownership type